Design of Steganographic Applications in A Processed Image using Algorithm Dynamic Markov Compression - Akmal Dirgantara Lubis; Garuda Ginting; Fadlina Fadlina (STMIK Budi Darma, 2020)
Confidential text data is an important matter that needs to be protected and kept confidential. Secret text data is a treasure where many people who want to try to find out first find out its contents. Therefore it is not uncommon for crimes to appear intentionally committed by irresponsible people. With the increasing number of people who commit crimes who deliberately steal confidential data and damage confidential text data so that it can harm certain parties. There have been several attempts to deal with the issue of security of confidential data sent over the internet, including using cryptographic and steganographic techniques